2020
DOI: 10.4103/ijo.ijo_948_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of endogenous endophthalmitis at a quaternary referral centre in south India

Abstract: Purpose: The purpose of this study is to evaluate the clinical profile, visual, anatomical and survival outcome of patients with endogenous endophthalmitis. Methods: Retrospective chart review of consecutive cases with endogenous endophthalmitis presenting from 2009-2016. Results: In our study, 41 eyes of 34 patients were included. Most common co-morbidity associated with endogenous endophthalmitis was Diabetes Mellitus (70.7%) and most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Bilateral eye involvement was more prevalent in endogenous fungal endophthalmitis than in bacterial endophthalmitis. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral eye involvement was more prevalent in endogenous fungal endophthalmitis than in bacterial endophthalmitis. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, endogenous endophthalmitis made up approximately 5.0% to 10% of all endophthalmitis case. [1][2][3] Of the endogenous cases, approximately 20% to 60% were caused by fungi, [3][4][5] with Candida albicans and Aspergillus flavus being the most common pathogens, together accounting for about 50% to 70% of fungal endophthalmitis. [3,6,7] In most cases, endogenous fungal endophthalmitis is the result of immunosuppression coinciding with fungemia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] A retrospective review from a quaternary referral center in south India reported an even distribution of fungi and bacteria among the culture-positive cases of EE. [ 3 ] 76.93% bacterial isolates were attributed to Gram-positive bacteria, of which Staphylococcus aureus was the most common and 23.07% were due to Gram-negative bacteria. Aspergillus species was the most common fungus that was isolated (53.8%) followed by Candida albicans (30.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus species was the most common fungus that was isolated (53.8%) followed by Candida albicans (30.7%). [ 3 ] Further, perinephric abscess is usually due to Gram-negative enteric bacilli or a polymicrobial infection due to Escherichia coli, Staphylococcus aureus , and Klebsiella pneumonia . [ 3 4 5 ] Candida albicans and Aspergillus are commonly seen fungi which account for 11.1% to 17.54% of total EE cases in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation